The effectiveness of dexmedetomidine for preventing acute kidney injury after surgery: a systematic review and meta-analysis - Zhao, Jing; Tang, Ming-hao; Shen, Qi-hong; Xu, Ding-chao (Frontiers in Medicine, 2024)
Background: Postoperative acute kidney injury (AKI) is a serious and distressing complication connected to various adverse outcomes following the surgical operation.Controversy remains regarding the dexmedetomidine's preventive impact on postoperative AKI. Therefore, this investigation aims to explore the efficiency and safety of dexmedetomidine in preventing AKI after surgical operation.We systematically searched electronic databases such as PubMed, Embase, Web of Science, and the Cochrane Library to detect eligible randomized controlled studies that used dexmedetomidine for the prevention of AKI following operation up to April 30, 2023. The main outcome evaluated was AKI incidence. The evidence quality was assessed employing the Grading of Recommendations Assessment, Development, and Evaluation.The meta-analysis included 25 trials, including 3,997 individuals. Of these, 2,028 were in the dexmedetomidine group, and 1,969 were in the control group. The result showed that patients administered dexmedetomidine significantly decreased the AKI incidence following surgical operation in contrast to the control group (risk ratio, 0.60; 95% confidence intervals, 0.45-0.78; P <0.05; I 2 = 46%). In addition, dexmedetomidine decreased the period of hospitalization in both the intensive care unit (ICU) and the hospital while also reducing postoperative delirium (POD) occurrence. However, dexmedetomidine elevated the incidence of bradycardia but did not have a significant impact on other indicators.Our meta-analysis indicates that the dexmedetomidine treatment reduces the postoperative AKI and POD risk while also shortening the time of hospitalization in the ICU and hospital. However, it is connected to an increased bradycardia risk.